If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=6n+9
We move all terms to the left:
3-(6n+9)=0
We get rid of parentheses
-6n-9+3=0
We add all the numbers together, and all the variables
-6n-6=0
We move all terms containing n to the left, all other terms to the right
-6n=6
n=6/-6
n=-1
| 44+(x+10)=180 | | 4(x+6)-5=19 | | -2x-8=-14 | | -1.3=y/3+3.5 | | 15+1=-4(8x-4) | | -2x–8=-14 | | 5y-3y=3y+5 | | 4÷(y-7)=5 | | 2(4x+6)=-47+27 | | 4+3(2x-3)=6x-5 | | 8x+40=6x=12 | | 5(3x+8)=-41+6 | | 2x+(-11)+73=180 | | 2x+-11)+73=180 | | x-27=8+18 | | (-8y-12y)=9 | | (2x+5)=(5x+28) | | 2x+5x=21+7 | | -5p+1=-39 | | 6w-12+2w=28 | | 27x+81=27x+81 | | 1800=24x | | -35(b-5)=24 | | 16x+32=8x+32 | | 5x+54=54 | | r+4/2=1 | | -x–1=-7 | | 2x7=x2 | | -15k+20=-20−20k+3k | | -4y=-10−9y | | -18+b=-b+20 | | -9m=8−7m |